American uprising [compact disc, unabridged] : the untold story of America's largest slave revolt - Rasmussen, Daniel, 1987- (Tantor Media, 2011)
A gripping and deeply revealing history of an infamous slave rebellion that nearly toppled New Orleans and changed the course of American history.